FUNGSI DAN PERAN BPOM DALAM PERLINDUNGAN KONSUMEN TERHADAP MAKANAN YANG MENGANDUNG BAHAN BERBAHAYA DI KOTA SEMARANG - Atin Carolina Parei; Fitika Andraini (Fakultas Hukum Universitas Stikubank, 2018)
The issue of legal protection for consumers is one that is championed in order to provide protection for the community as consumers. BPOM Semarang City has the duty to provide services for the community to supervise the circulating products to ensure their safety, however, there are still products that contain hazardous substances in circulation. Therefore this thesis is entitled